2020
DOI: 10.3389/fpsyg.2020.01398
|View full text |Cite
|
Sign up to set email alerts
|

Happy Little Benefactor: Prosocial Behaviors Promote Happiness in Young Children From Two Cultures

Abstract: Evidence that young children display more happiness when sharing than receiving treats supports that humans, by nature, are prosocial. However, whether this "warm glow" is also found for other prosocial behaviors (instrumental helping and empathic helping) and/or in different cultures is still unclear. Dutch (studies 1 and 2) and Chinese (study 3) young children participated in a sharing task, followed by instrumental helping and empathic helping tasks in which they were praised (thanked) if they helped. Consi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 47 publications
0
29
0
Order By: Relevance
“…Video recordings of the toddlers’ interactions were later coded for facial expressions of happiness. Analyses revealed that children smiled more when giving an edible treat to a puppet than when receiving edible treats themselves, suggesting that the emotional rewards of giving are detectable early in childhood (Aknin, Hamlin, & Dunn, 2012; see also Aknin, Broesch, Van de Vondervoort, & Hamlin, 2015; Song Broekhuizen, & Dubas, 2020).…”
Section: Helping and Happiness: An Overviewmentioning
confidence: 99%
“…Video recordings of the toddlers’ interactions were later coded for facial expressions of happiness. Analyses revealed that children smiled more when giving an edible treat to a puppet than when receiving edible treats themselves, suggesting that the emotional rewards of giving are detectable early in childhood (Aknin, Hamlin, & Dunn, 2012; see also Aknin, Broesch, Van de Vondervoort, & Hamlin, 2015; Song Broekhuizen, & Dubas, 2020).…”
Section: Helping and Happiness: An Overviewmentioning
confidence: 99%
“…The toddlers' behaviour was video recorded throughout, and facial expressions were later coded for happiness by a team of trained coders. Analyses revealed that toddlers smiled more when giving treats away to the puppet than when receiving treats themselves, both when kids gave their own treat or an identical treat provided by the experimenter, suggesting that toddlers find giving emotionally rewarding ; see also Song et al, 2020). Other research converges with the notion that young children find prosocial action rewarding.…”
Section: Do Real-world Prosociality Programs Predict Greater Psychological Well-being In Kids?mentioning
confidence: 88%
“…In most studies investigating the link between children's positive emotions and their prosocial behavior, children were given an opportunity to share with or help a social partner and their emotion was measured before or thereafter. These studies have found that 2-to 5-year-old children express positive emotions, that is a higher level of happiness, as assessed by raters, while sharing a reward with a puppet (Aknin et al, 2012(Aknin et al, , 2015Song et al, 2020). This response has been found to emerge in children from two Western cultures (the United States and the Netherlands; Aknin et al, 2012;Song et al, 2020), and in children from a rural smallscale society (Aknin et al, 2015).…”
Section: How Being Observed Influences Preschoolers' Emotions Following (Less) Deserving Helpmentioning
confidence: 96%
“…Emotions play a pivotal role in motivating and maintaining children's prosociality (Eisenberg et al, 2016;Malti & Dys, 2018). For instance, sympathy for those who have been harmed increases children's comforting (Eisenberg & Miller, 1987;Malti et al, 2009;Vaish et al, 2009;Zahn-Waxler et al, 1992) and children show positive emotions when helping and giving to others (Aknin et al, 2012(Aknin et al, , 2015(Aknin et al, , 2018Hepach et al, 2017;Lennon & Eisenberg, 1987;Song et al, 2020;Wu et al, 2017). These positive emotions appear to provide a proximate incentive for children to forego their immediate self-interest, and instead invest in their cooperative partners (Aknin et al, 2012), as well as maintain their relationships with peers, e.g., by signaling interest in cooperative interactions (Marcus, 1986).…”
Section: How Being Observed Influences Preschoolers' Emotions Following (Less) Deserving Helpmentioning
confidence: 99%
See 1 more Smart Citation